Morphometric evaluation of Aedes aegypti (Linnaeus, 1762) and Culex quiquefasciatus (Say, 1823) (Diptera: Nematocera: Culicidae) of different metamorphosis stages (Bangladesh Journal of Zoology, 2024)
Morphometric comparison of Aedes. aegypti and Culex. quiquefasciatus larval instars and pupae were done through the measurements of total body length, length of head, thorax and abdomen as well as length and width of different external body parameters.   From linear regression of the data from different larval instars showed that the important morphological features were the size of the head, thorax and abdomen of the Ae. Aegypti and Cx. Quinquefasciatus.  They increased significantly with the advanced metamorphosis stages (p≤0.05). Size of the external larval organs viz. antennae, comb spine, siphon, anal papilla were also significantly (p≤0.05) increased during stages of metamorphosis.Bangladesh J. Zool. 51(3): 329-343, 2023